An integrated transcriptomic and metabolomic atlas reveals the temporal regulation of benzylisoquinoline alkaloid biosynthesis and transport in developing opium poppy capsules - Wang, Qian; Qie, Xiaofang; Zhen, Yun; Li, Ruoshi; Liu, Zhaoyu; Zhang, Yanjun; Chen, Shilin; Song, Chi (Frontiers in Plant Science, 2026)
IntroductionThe opium poppy (Papaver somniferum L.) is the primary source of medically important benzylisoquinoline alkaloids (BIAs), including morphine and codeine. Nevertheless, the transcriptional regulatory networks and transport processes underlying the spatiotemporal accumulation of BIAs during capsule development remain incompletely understood.MethodsWe performed an integrated transcriptomic and metabolomic analysis across five defined capsule developmental stages (S1–S5). Transcript–metabolite relationships were examined using global correlation analysis, trend analysis, and weighted gene co-expression network analysis (WGCNA). To identify putative BIA transporters, we applied a multi-tiered bioinformatic screening pipeline that combined hub-gene prioritization, transmembrane domain prediction, and functional annotation, followed by qRT-PCR validation of shortlisted candidates.ResultsMetabolomic profiling revealed a clear developmental trajectory of BIA accumulation, with S4 emerging as a critical stage for BIA biosynthesis. Terminal alkaloids reached maximal levels at S4 and declined sharply at S5, suggesting the initiation of active transport and/or metabolic conversion at late development. Strong transcript–metabolite concordance enabled robust multi-omics integration. WGCNA identified 32 co-expression modules, among which the steelblue, brown, blue, and white modules showed the strongest associations with BIA metabolites, including the key intermediate thebaine. The integrated screening strategy and qRT-PCR validation ultimately highlighted PsMATE1 and PsEXS1 as the highest-confidence transporter candidates, supported by their multiple predicted transmembrane domains, membership in established transporter families, and expression patterns tightly synchronized with late-stage BIA accumulation.ConclusionThis study provides a comprehensive multi-omics resource and a systematic framework for transporter discovery in P. somniferum capsules. The identification of PsMATE1 and PsEXS1 offers prioritized targets for future functional characterization and advances understanding of the mechanisms controlling BIA transport and accumulation during capsule development.